Social Work Educators as Transformational Leaders - Park, Tae Kyung (Journal of Social Work Education and Practice, 2024)
While teacher leadership is novel in the context of social work education, it has been studied in educational literature for decades as an effective characteristic to improve both teachers’ competence and student learning outcomes. This paper suggests that social work education adopt teacher leadership in the classroom by viewing a classroom as a learning community in order to train social work students and those who pursue continuous education in community organizations, including nonprofit organizations such as grassroots agencies and social administration. Among leadership models, the transformational leadership style is recommended as an effective teacher-leader model. This paper demonstrates how the four components of transformational leadership can help social work teachers motivate, encourage, and improve student learning.